KARAKTERISTIK MUTU FISIK TEKWAN KERING DENGAN RASIO IKAN BERBEDA - Muhammad Irfan Febriansyah; Sukarno Sukarno; Dedi Fardiaz (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Dried tekwan is a traditional restructured-fish product of South Sumatera processed by convectional drying. The study aimed to determine the effect of fish and tapioka ratio and tekwan’s length on the physical quality of the dried tekwan. The physical quality of dried tekwan made with different ratio of fish and tapioca ratio (1:1, 1.5:1 and 2:1 (w:w)) and length 1, 2, and 3 cm were investigated. The physical quality evaluated were the degree of whiteness, rehydration ratio, water holding capacity (WHC) and microstucture. The drying profile and proximate composition were also evaluated. There was no difference in the rate of drying of different fish:tapioca ratio as well a different tekwan length when free water evaporation was progressing. However, difference in drying rate was observed when the water content reached the equilibrium. Ratio 2:1 of fish and tapioca and 2 cm length of tekwan was found the to be best treatment and resulting in dried tekwan with moisture content 10.22%, ash 1.9%, protein 27.9%, fat 1.38%, carbohydrate 58.6%, whiteness 45.96% and expressible moisture content 2.06%. Microstructure of dried tekwan with 2:1 ratio showed more compact structure and slight damage than 1.5:1 ratio. However, dried tekwan with 2:1 ratio still had lower rehydration properties than other treatment.